2021
DOI: 10.3390/rs14010044
|View full text |Cite
|
Sign up to set email alerts
|

Integrity Monitoring of PPP-RTK Positioning; Part I: GNSS-Based IM Procedure

Abstract: Nowadays, integrity monitoring (IM) is required for diverse safety-related applications using intelligent transport systems (ITS). To ensure high availability for road transport users for in-lane positioning, a sub-meter horizontal protection level (HPL) is expected, which normally requires a much higher horizontal positioning precision of, e.g., a few centimeters. Precise point positioning-real-time kinematic (PPP-RTK) is a positioning method that could achieve high accuracy without long convergence time and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…In this study, the risks of incorrect ambiguity fixing are considered as ignorable. While this assumption is widely used in existing studies (Jokinen et al, 2013a;Jokinen et al, 2013b;Feng et al, 2014;Wang et al, 2020;Wang et al 2022;Gao et al, 2021), the effects of wrong ambiguity fixing on the protection level computations are analyzed in Sect. "Effects of fault probabilities on protection level computations".…”
Section: Fault Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the risks of incorrect ambiguity fixing are considered as ignorable. While this assumption is widely used in existing studies (Jokinen et al, 2013a;Jokinen et al, 2013b;Feng et al, 2014;Wang et al, 2020;Wang et al 2022;Gao et al, 2021), the effects of wrong ambiguity fixing on the protection level computations are analyzed in Sect. "Effects of fault probabilities on protection level computations".…”
Section: Fault Modelsmentioning
confidence: 99%
“…Before the implementation, stochastic models, fault probabilities, PHMI, and false alarm rates should be defined priorly. Based on the existing research (Blanch et al, 2015;Racelis & Joerger, 2020;Wang et al, 2022;Working Group C, 2016), these parameters are set as in Table 3. It is worth mentioning that nominal biases and standard deviations of uncombined observations are still under investigation, we use a conservative setting which is usually used for IF combinations for them.…”
Section: Experimental Settingsmentioning
confidence: 99%
“…To ensure the precision of the ambiguity parameters, the ambiguity with a lower elevation angle of 15 degrees or with a STD value larger than one cycle will be rejected in the ambiguity resolution. In AR processing, the WL ambiguity is first fixed by rounding, and then the NL ambiguity by LAMBDA (Least-square AMBiguity Decorrelation Adjustment), with the ratio value threshold of 3 for ambiguity validation (Teunissen and Verhagen 2004;Wang et al 2022).…”
Section: Data and Experiments Descriptionmentioning
confidence: 99%
“…However, this STD may be vulnerable to gross error because it is calculated with few ionosphere observations. Wang et al (2022) analytically studied the form of the variancecovariance matrix of ionosphere interpolation errors for both accuracy and integrity purposes, which considers the processing noise, the ionosphere activities, and the network scale. How to properly determine the a priori precision for the interpolated ionospheric delay still needs further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 7 ] discovered that having more LEO satellites leads to a shorter convergence time, and the convergence time can be shortened from 8.2 to 0.8 min by introducing observations from 288 polar-orbiting LEO satellites. The results of Wang et al [ 8 , 9 ] showed that the LEO augmentation could be significantly reduced the convergence time of the ambiguity-float formal horizontal precision. Secondly, LEO signal augmentation can provide new observations.…”
Section: Introductionmentioning
confidence: 99%